Modelling and Analysis of Ziegler-Nichols and Chien-Hrones-Reswick Tuning PID on DC Motor Speed Control - Reza Sarwo Widagdo; Balok Hariadi; Kukuh Setyadjit (Jurnal Teknologi Elektro, 2023)
There have been many studies on the methods used to control DC motors, one of which is the proportional-integral-derivative (PID) control method. The tuning procedure is carried out by trial and error whose results are not necessarily correct, to overcome this problem an alternative is needed that can achieve a better and faster value for the tuning process. Our contribution is explained the conventional PID (Ziegler - Nichols) and modificated PID (Chien - Hrones - Reswick). We also analyze the response of the speed-controlled DC motor using the Proportional, Integral, and Derivative parameters obtained from the tuning method described above. We also discuss the advantages and disadvantages of each formula of these methods. Implementing both methods using a Matlab, creating a more convenient and user-friendly environment for engineering students and practicing engineers to better understand the formulas of his PID controller tuning method.